The Nonprofit Sport Businesses in Hungary - Orbán, Szabolcs Gergely; Szabados, György Norbert; Dajnoki, Krisztina (International Journal of Engineering and Management Sciences, 2018)
Over the past decade, leisure activities have expanded considerably, with a strong role to play in sport, on the one hand, by the popularity of traditional sports and on the rapid spread of emerging extreme sports. This active activity is a means of spending leisure time, and community building, health preservation, and the ability to develop work capacity are socially negligible. One of our aims is to find out whether nonprofit-making sports organizations can compete in the nonprofit sector with other members of the sector, using the complex statistic database of the CSO recently issued for the nonprofit sector, we also show how these enterprises have undergone progress in recent years and what current social and economic weight they are as part of the third sector.